QuantiFERON® TB Gold IT in the diagnosis of active pulmonary TB - Clara Fabris; Adriana Abrami; Daiana Bevilacqua; Tiziana Bordon; Franca Cian; Bruno Biasioli (Microbiologia Medica, 2010)
The IGRAs (Interferon-γ Release Assays) are commercial assays which measure T-cell-mediated response in vitro after specific stimulation, and represent the alternative to TST (Tuberculin Skin Test) in the diagnosis of latent tuberculosis infection (ILTB) and of active tuberculosis (TB). Among these we choose the assay QuantiFERON ®-TB Gold IT (Cellestis Ltd, Carnegie,Victoria, Australia) (QFT) in which interferon-γ (IFN-γ) was measured after lymphocyte stimulation with 3 antigens of the RD1 region of M. tuberculosis: ESAT-6, CFP-10 and TB 7.7. We wanted to assess the sensitivity of the method in cases of pulmonary TB, using cultured isolates of M. tuberculosis as gold-standard. From August 2006 to July 2009 there were 54 suspected cases of pulmonary TB, confirmed by culture.The QFT was requested for 32 patients before any microbiological confirmation and therapy. Of these patients 14 aged 20-50 years, 6 aged 50-70 years and 12 were more than 70-year-old. The QFT was positive in 25 patients (INF-γ> 0.35 IU/mL) and negative in 7 patients (INF-γ <0.35 IU/mL) while 2 patients had an INF-γ value of 0.34 IU/mL. Susceptibility to pulmonary TB is very high in young subjects and decreases with increasing age. In elderly population it is frequent a TB reactivation due to a decline in T-cell-immune response.Therefore, a negative or borderline value of IFN-γ should be interpreted with care.